1992
DOI: 10.2307/3869567
|View full text |Cite
|
Sign up to set email alerts
|

The Tomato 66.3-kD Polyphenoloxidase Gene: Molecular Identification and Developmental Expression

Abstract: A gene coding for a polypeptide abundant in tomato floral meristems was isolated and shown to represent a tomato 66.3-kD polyphenoloxidase. Analysis of cDNA clones and a corresponding intronless genomic clone indicated that the plastid-bound 587-residue-long polypeptide, designated P2, contains two conserved copper-binding domains, similar to those found in funga1 and mammalian tyrosinases. P2 transcripts and polypeptides are accumulated in the arrested floral primordia of the anantha mutant inflorescences and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 0 publications
7
33
0
Order By: Relevance
“…This was suggested to be the precursor of the 59-kD purified trichomal PPO (Kowalski et al, 1992) and was further supported by the structure of cDNA clones isolated from potato (Hunt et al, 1993). Cloned tomato PPO genes appeared to code for 66.1-to 70.6-kD precursors of 57.0-to 61.6-kD mature products (Shahar et al, 1992;Yu, 1992;Newman et al, 1993). Gary et al (1992) reported recently that a full-length V. faba PPO cDNA clone had a predicted mature molecular mass of 58 kD.…”
Section: Thylakoid Lumen By the Conventional Mechanismsmentioning
confidence: 83%
See 2 more Smart Citations
“…This was suggested to be the precursor of the 59-kD purified trichomal PPO (Kowalski et al, 1992) and was further supported by the structure of cDNA clones isolated from potato (Hunt et al, 1993). Cloned tomato PPO genes appeared to code for 66.1-to 70.6-kD precursors of 57.0-to 61.6-kD mature products (Shahar et al, 1992;Yu, 1992;Newman et al, 1993). Gary et al (1992) reported recently that a full-length V. faba PPO cDNA clone had a predicted mature molecular mass of 58 kD.…”
Section: Thylakoid Lumen By the Conventional Mechanismsmentioning
confidence: 83%
“…The active form of PPO was frequently reported to be about 45 kD (Vaughan et al, 1975;Lanker et al, 1987), but other forms, e.g. 59 and 65 to 68 kD were also reported Ganesa et al, 1992;Shahar et al, 1992). PPOs appear to be encoded by gene families .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was suggested recently that the sequence could have been derived from polyphenol oxidase (PPO) that had not been separated from the kinase on SDS-PAGE (I. Ohad, unpublished). The mature PPOs from other plants have similar N-terminal sequences [10][11][12][13]. Thus, the 60-kDa protein is likely to be identical to PPO.…”
Section: Discussionmentioning
confidence: 97%
“…Cloning of cDNAs and genes yielded deduced amino acid sequences that indicated that the protein is translated as a precursor with a transit sequence that would direct the precursor into the thylakoid lumen [10][11][12][13]. Nevertheless, the physiological function of this protein remains to be established [14] because there is no reason to believe that o-diphenol substrates of PPO would be present in the thylakoid lumen.…”
Section: Discussionmentioning
confidence: 99%